Reduce Inventory Cost by Implementation of Just In Time Method In Raw Materials Inventory Control Website Application - Naila Hida Kholik; Endra Rahmawati; Pantjawati Sudarmaningtyas (Universitas Budi Darma, 2023)
The production process is the main activity of a manufacturing company, and one of the success factors of production is good raw material inventory management. One of the problems is the inefficiency of using raw materials that impacted raising inventory costs caused by the large number of raw materials left in the warehouse. This study aims to reduce inventory costs by embedding the Just in Time (JIT) method in the inventory application to calculate the raw material inventory. The application of the JIT method will consider 5 things, namely optimal number of shipments, order quantity per order, delivery quantity, frequency of raw material purchases and total inventory costs with JIT.The analysis used data from 2019-2021, proving the JIT could reduce the total inventory cost by 92%. In 2019 the total inventory cost decreased from Rp. 6.773.533 to Rp. 829.976. JIT is able to lower the total inventory cost in 2020 and 2021 by 93% and 96%. The application testing results using Black Box shows that all application features can be used properly and accordingly. It’s supported by the percentage of the trial pass value reaching 100%. Based on those results, it can be concluded that the established built inventory application was appropriately used, accordingly, and effectively to reduce the inventory cost.